Determinants influencing healthcare workers' anxiety levels during the COVID-19 pandemic at Cut Nyak Dhien Regional General Hospital, West Aceh - Tari, Nadalia Indah; Hidayat, Melania; Zakaria, Radhiah; Maidar, Maidar; Abdullah, Asnawi (Institute of Computer Science (IOCS), 2024)
The COVID-19 pandemic has had a significant impact on society, particularly on healthcare professionals who have been at the forefront of the pandemic response. They have faced a high risk of virus exposure and have been burdened with extraordinary responsibilities in saving lives. Since the onset of the pandemic until February 2022, thousands of healthcare workers have been exposed to the virus, and some have even lost their lives. Therefore, this study was conducted to understand the factors influencing the level of anxiety among healthcare workers during the COVID-19 pandemic. The research employed a cross-sectional survey approach and was conducted at Cut Nyak Dhien Regional General Hospital, West Aceh Regency, in November 2021. The study population consisted of 396 healthcare workers, with a sample of 304 healthcare workers selected using purposive sampling. Data collected were analyzed using logistic regression. The findings revealed that the majority of healthcare workers at Cut Nyak Dhien Hospital experienced high levels of anxiety during the COVID-19 pandemic, with 72.37% experiencing panic anxiety, while 27.63% experienced non-panic anxiety. Significant factors influencing anxiety levels included family support, with an odds ratio (OR) of 2.1 and a p-value of 0.017, sufficient knowledge with an OR of 0.5 and a p-value of 0.084, and adequate provision of Personal Protective Equipment (PPE) with an OR of 2.1 and a p-value of 0.026. However, there was no significant relationship between anxiety levels and variables such as age, profession, marital status, highest education level, and comorbid conditions.